2010
DOI: 10.2337/dc10-1095
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus Alone in the Absence of Subsequent Diabetes Is Associated With Microalbuminuria

Abstract: OBJECTIVEWomen with gestational diabetes mellitus (GDM) maintain a higher risk for recurrent GDM and overt diabetes. Overt diabetes is a risk factor for development of chronic kidney disease (CKD), but GDM alone, without subsequent development of overt diabetes, may also pose a risk for CKD.RESEARCH DESIGN AND METHODSThis cross-sectional analysis included Kidney Early Evaluation Program (KEEP) participants from 2000 to 2009. Patient characteristics and kidney function among three categories (GDM alone, overt d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 23 publications
4
38
1
Order By: Relevance
“…GDM alone (without subsequent type 2 DM) was found as a risk factor for future development of microalbuminuria. In addition to microalbuminuria, the authors reported that patients with a history GDM had an increased risk for developing future CKD (27). Although this study used a relatively large cohort, it was based on self-report data.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…GDM alone (without subsequent type 2 DM) was found as a risk factor for future development of microalbuminuria. In addition to microalbuminuria, the authors reported that patients with a history GDM had an increased risk for developing future CKD (27). Although this study used a relatively large cohort, it was based on self-report data.…”
Section: Discussionmentioning
confidence: 96%
“…In the first study, Friedman et al (26) followed 72 patients for 5 to 8 years after the last GDM occurrence and reported a higher risk for microalbuminuria in women with a history of GDM than in the control group. The second study by Bomback et al (27) was a relatively large cohort study (571 women with GDM vs 25 045 women without GDM) that was based on selfreport data. GDM alone (without subsequent type 2 DM) was found as a risk factor for future development of microalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…In the Kidney Early Evaluation Program (KEEP), women who reported a history of GDM but without subsequent known diabetes had a higher prevalence of microalbuminuria at mean age 51.5 years than did their peers who did not have previous GDM (13). In the Third National Health and Nutrition Examination Survey (NHANES), women with a self-reported history of GDM (n ϭ 85) had higher urine MA/creat than those without such a history (14).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, previous studies have reported that women with a history of previous GDM have higher levels of urinary microalbumin than women who do not have a history of GDM, when evaluated between 5 to 11 years after the index pregnancy (13)(14)(15)(16). However, a confounding factor that has not been considered in these studies is the potential impact of concomitant glucose intolerance.…”
mentioning
confidence: 88%
“…2 Women with a history of gestational diabetes are at increased risk of cardiovascular and kidney disease, regardless of whether they have gone on to develop overt diabetes, growing evidence suggests. 3 Crowther et al and London et al have reported fetal death with gestational diabetes. 4,5 However underlying cause of intrauterine death in mothers with gestational diabetes are unclear.…”
Section: Introductionmentioning
confidence: 98%